Race, ethnicity, and structural variations in youth risk of arrest: evidence from a national longitudinal sample - Stevens Andersen, Tia (Criminal justice and behavior, 2015)
Missing from the considerable body of literature on disproportionate minority contact is an examination of the factors that influence risk of juvenile arrest. Using the National Longitudinal Survey of Youth 1997, the author examines racial/ethnic disparities in youth arrest, net of self-reported delinquency. Drawing from research using a minority threat perspective, this study examines whether disparities are exacerbated by macro levels of the relative size of the minority population and minority economic inequality. The results indicate Black youth have a higher risk of arrest than White youth in all contextual climates, but this disparity is magnified in predominantly non-Black communities. Differences between Hispanic and White youths? risk of arrest did not reach statistical significance or vary across communities. The findings failed to yield support for the threat perspective but strongly supported the benign neglect thesis. Implications for theory and future research are discussed.